Early failure of prosthetic valve presenting with acute heart failure - P Candela; L Ajello; MCE Valerio; P Camarda; V Mineo; EV Castelluccio; E Rebulla (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2023)
Background: Early failure of cardiac biological prostheses refers to the deterioration or malfunction of the valve sooner than expected. These prostheses are designed to last for many years, even decades, but in some cases, they may fail within a much shorter timeframe. Early failure can manifest in various ways, including structural issues, valve stenosis, regurgitation, and reduced functionality. Understanding the causes of early failure is crucial for improving patient outcomes. Case presentation: We present the case of failure of a biological prosthesis implanted five years prior; the onset was rapid and acute (worsening dyspnea three days before access to the emergency room). A transcatheter mitral valve replacement was planned. Unfortunately, the patient expired before the procedure.  Discussion: Although rare, early failure of biological valve prosthesis is possible. So, when treating a patient with a history of valve surgery presenting with acute heart failure, the suspicion of valve failure should be always considered.